Material Synthesis, Spectral, Optical and Antimicrobial Activity of Imidazolium Based Aldehydic Ionic Liquids: 1–Ethyl-3-methyl-2-(2-oxo-ethyl)-3H-imidazol-1-ium bromide (I) and 1-butyl-3-methyl-2-(2-oxo-ethyl)-3H-imidazol-1-ium chloride (II) - Sudhalakshmi, J.; Rajathi, D. K. (Journal of Scientific Research, 2023)
We successfully produced imidazolium aldehydes from imidazolium alcohols for the first time using copper wire and no oxidizing agents. The findings of IR, UV, 1H-NMR, and 13C-NMR spectral examinations all indicated complete Oxidation of the alcohols, which was further demonstrated by those findings. The oxidation technique was used to create the ionic liquids 1-ethyl-3-methyl-2-(2-oxo-ethyl)-3H-imidazol-1-ium; bromide and 1-butyl-3-methyl-2-(2-oxo-ethyl)-3H-imidazol-1-ium; chloride. Using elemental and spectral analyses confirmed the structure of the synthesized compounds (I) and (II). FT-IR analysis was used to determine the presence of functional groups in the grown samples (I) and (II), and 1H-NMR and 13C-NMR spectral analysis were performed to confirm the environment of the elements (C, H). A UV-Visible-NIR spectrophotometer was implemented to determine the optical absorption value for samples (I) and (II). Using DSC analysis, the thermal stability and decomposition were seen. Bacillus Cereus, Staphylococcus Aureus, Enterobacter Coacae, and Staphylococcus Haemolytics were used in an antimicrobial study for samples (I) and (II), and the results are compared with control Ciprofloxacin.